1999
DOI: 10.1105/tpc.11.9.1717
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Mitochondrial DNA Sequences of Nephroselmis olivacea and Pedinomonas minor: Two Radically Different Evolutionary Patterns within Green Algae

Abstract: Green plants appear to comprise two sister lineages, Chlorophyta (classes Chlorophyceae, Ulvophyceae, Trebouxiophyceae, and Prasinophyceae) and Streptophyta (Charophyceae and Embryophyta, or land plants). To gain insight into the nature of the ancestral green plant mitochondrial genome, we have sequenced the mitochondrial DNAs (mtDNAs) of Nephroselmis olivacea and Pedinomonas minor . These two green algae are presumptive members of the Prasinophyceae. This class is thought to include descendants of the earlies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(61 citation statements)
references
References 46 publications
2
59
0
Order By: Relevance
“…Alternative explanations would require the massive loss of some, followed by a gain of other, mitochondrial introns in at least one of the two lineages. This scenario appears less likely, most notably in light of the absence of homologous introns in completely sequenced green algal chondriomes (Wol et al 1994;Turmel et al 1999;KuÈ ck et al 2000;Nedelcu et al 2000). This observation apparently extends to algae of the Charophyceae, where we have so far found that introns are generally absent in nad genes (unpublished observations).…”
Section: Discussionmentioning
confidence: 52%
“…Alternative explanations would require the massive loss of some, followed by a gain of other, mitochondrial introns in at least one of the two lineages. This scenario appears less likely, most notably in light of the absence of homologous introns in completely sequenced green algal chondriomes (Wol et al 1994;Turmel et al 1999;KuÈ ck et al 2000;Nedelcu et al 2000). This observation apparently extends to algae of the Charophyceae, where we have so far found that introns are generally absent in nad genes (unpublished observations).…”
Section: Discussionmentioning
confidence: 52%
“…In such case, the intron must have been lost in F. eriococci. The intron is similar to a group of chloroplast and mitochondrial rRNA gene introns from chlorophyte algae (Everett et al, 1999b;Turmel et al, 1999Turmel et al, ,2002Lucas et al, 2001;Pombert et al, 2006). Members of Chlamydia have not yet been found in algae, so the intron might have originated from the food of its earlier host, as already suggested by Everett et al (2005).…”
Section: Phylogenetic Relationshipsmentioning
confidence: 95%
“…Isolation and sequencing of cpDNA A + T-rich organelle DNA was separated from nuclear DNA by CsCl-bisbenzimide isopycnic centrifugation (Turmel et al 1999a). Both the chloroplast and mitochondrial genomes were completely sequenced as described previously (Pombert et al 2004), using as templates plasmid clones originating from the organelle DNA fraction as well as PCR fragments spanning uncloned regions.…”
Section: Strain and Culture Conditionsmentioning
confidence: 99%